Developing deep learning in science classrooms: Tactics to manage epistemic uncertainty during whole‐class discussion - Chen, Ying‐Chih; Techawitthayachinda, Ratrapee (Journal of research in science teaching, 2021)
Science teachers usually view students' uncertainty as a barrier to overcome, a negative experience to be avoided, a deficiency in need of remedy. Building on the theory of deep learning in science as a generative and sensemaking process, the purpose of this design‐based study is to identify tactics for teachers to manage their students' epistemic uncertainty as a pedagogical resource to develop student conceptual understanding during whole‐class discussion. Classroom observations of whole‐class discussion were collected from six teachers' classes ranging from third to eighth grade. A total of 18 whole‐class discussions were collected, transcribed, and analyzed. A storyline talk to manage uncertainty during whole‐class discussion was developed and consisted of three stages: (1) Raise epistemic uncertainty through creating ambiguous conditions; (2) Maintain epistemic uncertainty through preventing immature disclosure and discussing alternative explanations or conflicting ideas; and (3) Reduce epistemic uncertainty through making coherent connections among current uncertainty, prior knowledge, and familiar phenomena. Seven nuanced tactics used by teachers to achieve each stage of uncertainty management were identified. The results suggest that managing uncertainty goes beyond asking questions and problematizing phenomena. When engaging students in storyline‐based whole‐class discussion, teachers should focus on one specific uncertainty and establish a coherent, consistent storyline that raises, maintains, and reduces student uncertainty to horizontally and vertically construct a collective knowledge among students. The horizontal nature occurs within a stage of management, and the vertical nature of a storyline talk is related to moving along from stage to stage. Through the storyline talk focusing on students' epistemic uncertainty, students can truly become agents in the learning process when the lesson is centered on and driven by students' uncertainty.